PEMANFAATAN LIMBAH CAIR SAGU UNTUK MEMPRODUKSI SELULOSA BAKTERI - Ahmad, Sitti Wirdhana; Yanti, Nur Arfa; Muhiddin, Nurhayani H. (Perhimpunan Biologi Indonesia, 2019)
ABSTRACTBacterial cellulose is an exopolysaccharide produced by bacteria and has a high purity level compared to plant cellulose and has unique structural and mechanical characteristics that can be utilized for various industrial purposes such as food, medical, plastic and paper. This study aims to determine the potential of sago liquid waste as a substrate for producing biocellulose and sugar concentration is required in producing bacterial cellulose from sago liquid waste. Production of bacterial cellulose from sago liquid waste was done with static condition for 14 days with treatment of sugar concentration 5,10,15 and 20% (w/v) using Acetobacter xylinum. Parameters were measured include of thickness, yield, crude fiber content and moisture content. Production of bacterial cellulose using sago liquid waste requires the addition of sugar as much as 10% with a thickness of 21.73 mm, yield of 34.97%, crude fiber of 4.5% and moisture content of 91.35%. Therefore, sago liquid waste is potentially used as a substrate for producing bacterial cellulose. Keywords :Biocellulose, nata, Acetobacter xylinum, Production substrate